Adhesion between high-strength concrete, epoxy resin and CFRP - Aguiar, J. L. Barroso de (2008)
This paper presents a study on the adhesion between high-strength concrete, epoxy resin and CFRP. The adhesion of the high-strength concrete was compared with the same property measured in conventional concrete. Shear tests were made to test adhesion from concretes to epoxy resin. Flexural tests were used to evaluate the adhesion between concretes, epoxy and CFRP. The effect of temperature was also evaluated. For ordinary temperatures (20 ºC) the results showed a better flexural performance of the CFRP reinforced high-strength concrete. However, the adhesion between concrete and epoxy resin was clearly affected with the increase of temperature.